Urban diversity and epidemic resilience: The case of the COVID-19. (March 2022) - Hananel, Ravit; Fishman, Ram; Malovicki-Yaffe, Nechumi
Abstract: The spread of the coronavirus pandemic offers a unique opportunity to improve our understanding of the role of urban planning strategies in the resilience of urban communities confronting a pandemic. This study examines the relationship between urban diversity and epidemiological resilience by empirically assessing the relation between the level of neighborhood homogeneity and the probability of being infected by the coronavirus. We focus on the ultra-Orthodox Jewish community in Israel, a relatively closed community that was disproportionately and severely affected by the pandemic. The findings indicate a monotonic but nonlinear relationship between the level of ultra-Orthodox prevalence in a neighborhood and a resident's probability of contracting COVID-19. As the fraction of ultra-Orthodox individuals in the neighborhood decreases, the fraction of infected population decreases significantly and more strongly that can be explained without recourse to urban diversity considerations. This relationship is found to be significant and strong, even when other variables are accounted for that had hitherto been perceived as central to coronavirus distribution, such as housing density, socioeconomic level of the neighborhood, and number of people per household. The findings are important and relevant to many societies around the globe in which a variety of populations have a separatist lifestyle. Highlights: The study examines the relationship between urban diversity and epidemiological resilience The Study focuses on the ultra-Orthodox community in Israel, a relatively closed community The UO community in Israel and elsewhere suffered from a high level of infections and mortality rates of COVID-19 the research examines the relationship between the level of neighborhood homogeneity and the probability of being infected by the coronavirus The research findings indicate a nonlinear relationship between the neighborhood's UOR and the probability of infection.